Atraumatic rupture of the spleen caused by Plasmodium falciparum, challenge in UN peacekeeping operations – a case report - Micković, Saša; Milojković, Goran; Stojiljković, Jugoslav; Borovčanin, Nemanja; Jović, Sanja; Kovačević, Saša (Vojnosanitetski pregled, 2024)
Introduction. Unlike traumatic rupture of the spleen, which is the most common consequence of blunt abdominal trauma and is well documented in the literature, and unlike the atraumatic rupture of the spleen, which is less common but also well described, spontaneous rupture of the spleen in a patient with malaria is a rare complication, with a potentially fatal outcome. Case report. A soldier aged 46 years, was hospitalized, with the clinical picture of abdominal colic and diarrhea, previously treated for a primary attack of acute malaria. During hospitalization, deterioration of health condition occurred, with the development of a clinical picture of an acute abdomen due to spontaneous rupture of the spleen which was successfully resolved by splenectomy. Conclusion. Splenectomy is the method of choice for patients with unstable clinical presentation due to atraumatic rupture of the spleen.